Efficacy of an ICALL tutoring system and process-oriented corrective feedback. Issue 2 (17th February 2016) - Choi, Inn-Chull
Abstract : A Web-based form-focused intelligent computer-assisted language learning (ICALL) tutoring system equipped with a process-oriented corrective feedback function was developed to investigate the extent to which such a program may serve as a viable method of teaching grammar to Korean secondary and elementary students. The present study was also intended to explore the overall efficacy of two different types of corrective feedback on errors made by students while using the process-oriented tutoring program. In addition, the current research attempted to identify the distribution pattern of errors made by English as a foreign language (EFL) learners across error types combining grammar and cognitive strategies. Finally, the research surveyed subjects' attitudes toward the ICALL tutoring program and assessed its ability to help them acquire grammatical concepts. Overall, the statistical analysis reveals that a form-focused ICALL tutoring system that provides process-oriented feedback may serve to facilitate EFL learners' acquisition of grammatical concepts, and that the majority of subjects think favorably of the ICALL tutoring program.